The return of the 'Black Babies': how development education affects schoolchildren's attitudes to the majority world – the Trócaire 2012 Lenten campaign. Issue 6 (2nd November 2019) - Sheridan, V.; Landy, David; Stout, Vanessa
Abstract: This article investigates how development education campaigns affect schoolchildren's understanding of both global and domestic poverty, through examining the 2012 Lenten campaign by the Irish agency, Trócaire. It analyses Trócaire campaign material as well as its reception by schoolchildren, aged 10–12. We found the material contained neo-colonial stereotypes about Africa as a primitive place dependent on Western aid, displaying continuity with the prior 'Black Baby Phenomenon'. This refers to the collection boxes Irish children were given with a picture of a black baby on them, which fostered an understanding of Africans as helpless childlike victims, Children in our focus groups understood the Africans portrayed by the Trócaire campaign as hopeless, primitive, intellectually inferior Others. Furthermore, this there was strong indication that this imagery fostered social distance towards ethnic minorities in Ireland and encouraged children to minimise domestic poverty, through considering this to be only an issue in 'developing countries'.